Zróżnicowanie strukturalne wybranych drzewostanów dębu szypułkowego ( Quercus robur L.) występujących na terenie Płyty Krotoszyńskiej - Szmyt, Janusz (Leśne Prace Badawcze, 2017)
The oak forests growing on the Krotoszyn Plateau are the biggest and most valuable oak forest complexes in Poland. The purpose of this study was to analyze the structural diversity of oak ( Q. robur L.) stands older than 140 years. Two natural stands located within the forest reserve as well as two managed stands were chosen for investigation. Species and tree size diversity were analyzed using different measures and spatially explicit and inexplicit indices. The results indicate that the structural diversity of the protected oak forests did not differ significantly from that of managed stands. On the contrary, undisturbed natural processes in protected forests can result in a low diversity of some structural attributes in such stands. Although most indices pointed towards a higher structural diversity in protected forests, the differences were not large, especially in the case of spatially explicit indices. The spatial arrangement of live trees was either random, aggregated or regular, with the latter clearly dominating managed, poorly mixed oak stands. Furthermore, a lack of natural disturbances strong hornbeam expansion, in which case strict protection is not favorable for oak sustainability as it creates unsuitable conditions for oak regeneration beneath the hornbeam canopy.